Perbandingan Kinerja Protokol Routing RIP (Routing Information Protocol) dan OSPF (Open Shortest Path First) Berbasis IPv6 - Muhammad Affan Alvyan; Primantara Hari Trisnawan; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Routing is the process of selecting the best route or route that must be passed so that packets get to the destination quickly. Most of the application of RIP and OSPF protocols on real networks and previous studies still use a lot of IPv4 networks, which we know is that the number of IPv4 address allocations in the world has decreased over the years. This study tries to use IPv6 addresses implemented in the RIP and OSPF routing protocols in the form of simulations in the Riverbed Modeler software to determine the performance of the two routing protocols by adding disconnections and recovery paths for sending data packets or failure recovery. The purpose of this study is to determine the best routing protocol in overcoming failure recovery from two IPv6-based RIP and OSPF routing protocols by comparing the performance of three parameters namely metric cost, convergence actvity, and routing traffic. The test results obtained from this study that the OSPFv3 routing protocol has a performance superior to RIPng in convergence activity and routing traffic. Difference in convergence activity speed of 8,59 seconds in scenario one and 3,39 seconds in scenario two. Difference in the average amount of traffic 153163,33 bps in scenario one and 109214,08 bps in scenario two. The conclusion from this study, that the best routing protocol in overcoming failure recovery is the OSPFv3 routing protocol. The metric cost parameter does not participate in determining the best routing protocol in overcoming failure recovery, because each routing protocol has its own algorithm in the routing process or has its own metric value in determining the best path that distinguishes between routing protocols.